From microanalysis to supercontinents: Insights from the Rio Apa Terrane into the Mesoproterozoic SW Amazonian Craton evolution during Rodinia assembly. (24th November 2021) - Ribeiro, Bruno V.; Finch, Melanie A.; Cawood, Peter A.; Faleiros, Frederico M.; Murphy, Timothy D.; Simpson, Alexander; Glorie, Stijn; Tedeschi, Mahyra; Armit, Robin; Barrote, Vitor R.
Abstract: Deciphering the tectono‐metamorphic evolution of Precambrian terranes can be difficult due to reworking by later superimposed events. Whole‐rock elemental and isotopic geochemistry and zircon U–Pb geochronology are often employed in those studies, but these approaches are often not sensitive to the presence of multiple events and medium‐grade metamorphic episodes. The Rio Apa Terrane (RAT), an allochthonous fragment of the Amazonian Craton, is a crustal block with a well‐characterized crustal evolution but with no detailed thermal constraints for its tectono‐metamorphic evolution. In contrast to previous studies, we show the existence of four tectono‐metamorphic events at c . 1, 780, c . 1, 625, c . 1, 420–1, 340, and c . 1, 300–1, 200 Ma on the basis of apatite, titanite, and rutile U–Pb, in situ white‐mica Rb–Sr, and in situ garnet Lu–Hf geochronology combined with mineral chemistry and phase‐equilibria modelling. The c . 1, 780 Ma event is recorded in the basement of the Western domain, representing an extensional event coeval with the development of its Eastern domain in response to the retreat stage of the accretionary system. This is followed by juxtaposition of the Western and Eastern domains along a major crustal boundary at c . 1, 625 Ma, which is defined by the magnetic profiles and zircon U–Pb–Hf data across the boundary. The third and fourth events correspond to progressive high‐pressure/medium‐temperature (HP/MT) metamorphism, characterized by an anticlockwise P–T path, suggesting a convergent‐to‐collisional tectonic setting. The RAT was accreted to the adjoining Paraguá Terrane at c . 1, 420–1, 340 Ma under an isobaric P–T evolution spanning ~530°C to 600°C and ~10.0 kbar. Subsequently, the combined Rio Apa and Paraguá terranes collided with the SW Amazonian Craton at c . 1, 300–1, 200 Ma, reaching P–T conditions of ~560–580°C and ~10.9–11.7 kbar during crustal thickening. This study reveals for the first time the existence of a HP/MT metamorphic evolution related to the growth of the SW Amazonian Craton as part of an accretionary orogenic system during Rodinia assembly in the Palaeoproterozoic to Mesoproterozoic.